Bioremediation potential of low-brominated polybrominated diphenyl by the phyllospheric Wickerhamomyces anomalus - Cai, Man; Xing, Zheng; Yuan, Xiaolei; Song, Zhangyu; Wang, Xiaojing; Du, Kejiu (Frontiers in Plant Science, 2025)
Phyllospheric microorganisms play a significant role in environmental bioremediation. However, there have been limited studies to assess the detoxification mechanisms of phyllospheric Wickerhamomyces anomalus in persistent organic pollutants (POPs), especially polybrominated diphenyl ethers (PBDEs). In this study, we performed RNA sequencing (RNA-seq) to identify the detoxification mechanism of 4-monobrominated diphenyl ether (BDE-3) and to identify abundant genes, differentially expressed genes, and promising candidates in phyllospheric yeast. The transcriptome analysis revealed that the potential detoxification genes were classified into four clusters: cell-wall binding, complexation, vacuolar sequestration, and efflux. The aim of this research was to study the functions of overexpressing heterologous yeast genes in plants. We identified possible candidate genes that may maintain high expression during vacuolar sequestration. The WICANDRAFT_64792 gene is a member of the ABC transporter family. The overexpressing WICANDRAFT_64792 (OW) tobacco seedlings exhibited higher photosynthetic rates and plant growth in alleviating BDE-3 stress than the wild type (WT). Vacuoles and the cytoplasm are the primary transportation and distribution storage organs for BDE-3. The deposition of BDE-3 in leaf cytoplasm and vacuoles prevented it from reentering the surrounding medium. The findings have substantial implications for using phyllosphere microbiome to improve plant stress tolerance.